Implementasi Ideologi Muhammadiyah dalam Tata Kelola dan Kebijakan Pendidikan Analisis Keputusan Organisasi, Masalah Lima, serta Khittah Muhammadiyah - Beni Zakaria Fitriyanto; Alfi Noer Diana Hafidah; Ahmad Syaifullah; Yasril Gunawan; Heri Rifhan Halili (INNOVASI : JURNAL INOVASI PENDIDIKAN, 2025)
This research aims to analyze the implementation of Muhammadiyah ideology in education governance and policy through organizational decisions, handling of Five Issues, and the practice of Muhammadiyah Khittah as a guideline for the movement. The ideology of Muhammadiyah not only functions as a system of theological ideas, but also as a normative and operational foundation that directs the implementation of Islamic education to progress. The approach of this research is qualitative descriptive with the method of literature study on official documents of Muhammadiyah, such as the Muhammadiyah Faith and Ideals of Life (MKCH), Muqaddimah of the Muhammadiyah Articles of Association (MADM), Khittah Muhammadiyah, as well as the decisions of the Congress related to the direction of organizational policies and educational development. The results of the study show that the ideology of Muhammadiyah is implemented applicatively in educational governance through organizational policies oriented towards the integration of faith, science, and charity. The Five Religions, Education, Economy, Politics, and Culture Issues function as a strategic framework in the development of Muhammadiyah education, while Khittah Muhammadiyah acts as a moral compass that keeps the implementation of education within the corridor of da'wah amar makruf nahi mungkar and independent of pragmatic interests.